Synthetic Cannabinoid-Induced Immunosuppression Augments Cerebellar Dysfunction in Tetanus-Toxin Treated Mice - Yun, Jaesuk; Gu, Sun Mi; Lee, Tac-hyung; Song, Yun Jeong; Seong, Seonhwa; Kim, Young-Hoon; Cha, Hye Jin; Han, Kyoung Moon; Shin, Jisoon; Oh, Hokyung; Jung, Kikyung; Ahn, Chiyoung; et al. (Biomolecules & therapeutics, 2017)
Synthetic cannabinoids are one of most abused new psychoactive substances. The recreational use of abused drug has aroused serious concerns about the consequences of these drugs on infection. However, the effects of synthetic cannabinoid on resistance to tetanus toxin are not fully understood yet. In the present study, we aimed to determine if the administration of synthetic cannabinoids increase the susceptibility to tetanus toxin-induced motor behavioral deficit and functional changes in cerebellar neurons in mice. Furthermore, we measured T lymphocytes marker levels, such as CD8 and CD4 which against tetanus toxin. JWH-210 administration decreased expression levels of T cell activators including cluster of differentiation (CD) 3ε, CD3γ, CD74p31, and CD74p41. In addition, we demonstrated that JWH-210 induced motor impairment and decrement of vesicle-associated membrane proteins 2 levels in the cerebellum of mice treated with tetanus toxin. Furthermore, cerebellar glutamatergic neuronal homeostasis was hampered by JWH-210 administration, as evidenced by increased glutamate concentration levels in the cerebellum. These results suggest that JWH-210 may increase the vulnerability to tetanus toxin via the regulation of immune function.